2023
DOI: 10.1002/mdc3.13666
|View full text |Cite
|
Sign up to set email alerts
|

Demographics and Clinical Characteristics of Autosomal Dominant Spinocerebellar Ataxia in Canada

Abstract: Background Autosomal dominant (AD) spinocerebellar ataxias (SCAs) encompass a large group of rare disorders, which occurs in individuals of different ethnic backgrounds. To date, demographics, and clinical descriptions of AD SCA in Canada are lacking. Methods A retrospective chart review of patients with a genetically confirmed diagnosis of AD SCAs was performed at five tertiary centers across Canada in the provinces of Quebec, Alberta, and Ontario. Demographic, genetic, and clinical information were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…45 In Quebec, a frequency of SCA27B as high as 60% has been reported among French-Canadian patients with previously unexplained adult-onset ataxia, making it the most common genetic cause of adult-onset ataxia in this population. 21,46 The observation of a common disease haplotype shared by some French-Canadian patients suggest that the high proportion of SCA27B in this population may correspond to a founder effect in this population known to be enriched for such effects. 47 Similarly, a previous study identified that three Australian patients shared a disease haplotype.…”
Section: Epidemiology and Regional Distributionmentioning
confidence: 93%
“…45 In Quebec, a frequency of SCA27B as high as 60% has been reported among French-Canadian patients with previously unexplained adult-onset ataxia, making it the most common genetic cause of adult-onset ataxia in this population. 21,46 The observation of a common disease haplotype shared by some French-Canadian patients suggest that the high proportion of SCA27B in this population may correspond to a founder effect in this population known to be enriched for such effects. 47 Similarly, a previous study identified that three Australian patients shared a disease haplotype.…”
Section: Epidemiology and Regional Distributionmentioning
confidence: 93%